Pengaruh Perputaran Kas, Perputaran Piutang, dan Perputaran Persediaan Terhadap Profitabilitas Dimoderasi oleh Ukuran Perusahaan - Indah Salsabillah Fa indra (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to determine cash turnover, accounts receivable turnover, and inventory turnover on profitability with firm size as a moderating variable in pharmaceutical and chemical companies listed on the Indonesia Stock Exchange in 2018-2023. The sample selection method used is purposive sampling. The total observations in this study were 102 samples with 6 years of observation consisting of 17 companies. The data analysis technique used in this research is moderation analysis using Moderated Regression Analysis. The test results of this research indicate that cash turnover, accounts receivable turnover, and inventory turnover simultaneously or together have an effect on profitability. Partially, cash turnover, accounts receivable turnover, and inventory turnover have a positive and significant effect on profitability. Firm size is able to moderate and strengthen the effect of inventory turnover on profitability. Firm size is not able to moderate and weaken the effect of cash turnover and accounts receivable turnover on profitability.